Joachim Lelewel’s Collections Journey from Kórnik to Vilnius - Leonavičiūtė, Inga (Lietuvos istorijos studijos, 2023)
Vilnius University Library possesses in its collections the personal library of distinguished historian, Joachim Lelewel (1786–1861), an alumnus and a professor of the Imperial University of Vilna. It consists of books, atlases, maps and other stocks gathered by Lelewel during his exile in Paris and Brussels. In his will, Lelewel bequeathed his library to Vilnius University, should that remembrance institution be restored. The library was temporarily stored at several locations, such as the Polish School at Batignolles (Paris), and Kórnik Library after 1874. In the fall of 1919 Vilnius University was reestablished by the Polish government under the name Stefan Batory University. The institution inherited former university’s meager library which had experienced heavy losses and deprivation during the decades of the Russian rule. Bringing to Vilnius extensive assets of printed and archival records gathered by the Polish emigrants in Western Europe through the 19th century was a great opportunity for the university library as it might significantly enrich its modest possessions. Lelewel’s personal library as well as Library and Archives of the Polish Museum at Rapperswil (Switzerland) were considered as first to be transferred. This article uses archival data to reconstruct almost a four-year long (February 1922 – end of 1925) journey of the Lelewel’s library from Kórnik to Vilnius.